A Rapid General Synthesis and the Spectroscopic Data of 2,2′-Bis-(di-isopropylphosphino)-1,1′-dibromoferrocene, (bpdbf), 1,1′,2,2′-Tetrakis-(di-isopropylphosphino) Ferrocene, (tdipf) and Related Ligands: Taking dppf into the Future - Peter N. Horton; Simon J. Coles; William Clegg; Ross W. Harrington; Ian R. Butler (Inorganics)
In this paper, the clean high yielding, synthesis, and structure of the tetraphosphine ligand, 1,1′,2,2′-tetrakis-(di-isopropyl-phosphino)ferrocene, (tdipf), is described. In addition, improved synthesis methods for 1,1′,2,2′-tetrakis(diphenylphosphino)ferrocene, (tppf), and 2,2′-bis-(diphenylphosphino)-1,1′-dibromoferrocene are also reported, and the synthetic method is generalised to include the synthesis of 3,3′-bis-(diphenylphosphino)-1,1′,2,2′-tetrabromoferrocene. The related ligands 2,2′-bis-(iso-propylphosphino)-1,1′-bis-diphenylphosphinoferrocene (diprdppf) and 2,2′-bis-(di-isopropylphosphino)-dibromoferrocene have also been prepared and characterised. The crystal structure of the square planar bimetallic nickel (II) dichloride of tdipf is also described, together with a brief NMR study investigating the synthesis of this and related metal complexes. The crystal structures of the palladium and platinum dichloride complexes of 2,2′-bis-(di-isopropylphosphino)-1,1′-dibromoferrocene, bpdbf, are also discussed in the context of comparison with previously known crystal structures in the same general family. A general discussion on the synthetic methodology is given, along with indications for future research that other researchers might explore.